Exercise cardiovascular magnetic resonance reveals reduced cardiac reserve in pediatric cancer survivors with impaired cardiopulmonary fitness - Foulkes, Stephen (J Cardiovasc Magn Reson, 2020)
BACKGROUND: Pediatric cancer survivors are at increased risk of cardiac dysfunction and heart failure. Reduced peak oxygen consumption (peak VO(2)) is associated with impaired cardiac reserve (defined as the increase in cardiac function from rest to peak exercise) and heart failure risk, but it is unclear whether this relationship exists in pediatric cancer survivors. This study sought to investigate the presence of reduced peak VO(2) in pediatric cancer survivors with increased risk of heart failure, and to assess its relationship with resting cardiac function and cardiac haemodynamics and systolic function during exercise. METHODS: Twenty pediatric cancer survivors (8–24 years; 10 male) treated with anthracycline chemotherapy ± radiation underwent cardiopulmonary exercise testing to quantify peak VO(2), with a value < 85% of predicted defined as impaired peak VO(2). Resting cardiac function was assessed using 2- and 3-dimensional echocardiography, with cardiac reserve quantified from resting and peak exercise heart rate, stroke volume index (SVI) and cardiac index (CI) using exercise cardiovascular magnetic resonance (CMR). RESULTS: Twelve of 20 survivors (60%) had reduced peak VO(2) (70 ± 16% vs. 97 ± 14% of age and gender predicted). There were no differences in echocardiographic or CMR measurements of resting cardiac function between survivors with normal or impaired peak VO(2). However, those with reduced peak VO(2) had diminished cardiac reserve, with a lesser increase in CI and SVI during exercise (Interaction P < 0.01 for both), whilst the heart rate response was similar (P = 0.71). CONCLUSIONS: Whilst exercise intolerance is common among pediatric cancer survivors, it is poorly explained by resting measures of cardiac function. In contrast, impaired exercise capacity is associated with impaired haemodynamics and systolic functional reserve measured during exercise. Consequently, measures of cardiopulmonary fitness and cardiac reserve may aid in early identification of survivors with heightened risk of long-term heart failure.